Attributes of a Relationship Management Model for the Public Sector (CiRS Exec) - Júlio Medeiros; Gisela Demo (BBR: Brazilian Business Review)
The New Public Management has encouraged the adoption of managerial tools by the public administration. In this context, the Citizen Relationship Management (CiRM) strategy allows for the improvement of the relationship with citizens and encourages citizenship. Thus, this research aims at identifying evidence for validity and reliability of a citizen relationship scale (CiRS Exec) for the Federal Executive Branch in Brazil, as well as a citizen’s satisfaction index. Exploratory and confirmatory factor analyses have been used, through structural equation modeling. The measurement model has presented good adjustment and a unifactorial structure scale named ‘Citizen Relationship’, comprising 13 items.